An observationally constrained evaluation of the oxidative capacity in the tropical western Pacific troposphere. Issue 12 (24th June 2016) - Nicely, Julie M.; Anderson, Daniel C.; Canty, Timothy P.; Salawitch, Ross J.; Wolfe, Glenn M.; Apel, Eric C.; Arnold, Steve R.; Atlas, Elliot L.; Blake, Nicola J.; Bresch, James F.; Campos, Teresa L.; Dickerson, Russell R.; et al.
Abstract: Hydroxyl radical (OH) is the main daytime oxidant in the troposphere and determines the atmospheric lifetimes of many compounds. We use aircraft measurements of O3, H2 O, NO, and other species from the Convective Transport of Active Species in the Tropics (CONTRAST) field campaign, which occurred in the tropical western Pacific (TWP) during January–February 2014, to constrain a photochemical box model and estimate concentrations of OH throughout the troposphere. We find that tropospheric column OH (OH COL ) inferred from CONTRAST observations is 12 to 40% higher than found in chemical transport models (CTMs), including CAM‐chem‐SD run with 2014 meteorology as well as eight models that participated in POLMIP (2008 meteorology). Part of this discrepancy is due to a clear‐sky sampling bias that affects CONTRAST observations; accounting for this bias and also for a small difference in chemical mechanism results in our empirically based value of OH COL being 0 to 20% larger than found within global models. While these global models simulate observed O3 reasonably well, they underestimate NO x (NO + NO2 ) by a factor of 2, resulting in OH COL 30% lower than box model simulations constrained by observed NO. Underestimations by CTMs of observed CH3 CHO throughout the troposphere and of HCHO in the upper troposphere further contribute to differences between our constrained estimates of OH and those calculated by CTMs. Finally, our calculations do not support the prior suggestion of the existence of a tropospheric OH minimum in the TWP, because during January–February 2014 observed levels of O3 and NO were considerably larger than previously reported values in the TWP. Key Points: Observations from the CONTRAST campaign in the tropical western Pacific are used to infer the concentration of tropospheric OH The empirically based value of tropospheric column OH is 0 to 20% larger than found within global models Underestimations of observed NO x, CH3 CHO, and HCHO drive most differences between column OH within global models and empirically based value